ANALISIS PEMANFAATAN E-RESOURCE DALAM PENINGKATAN MINAT BACA MAHASISWA DI PERPUSTAKAAN UNIVERSITAS ANDALAS - Yulianti, Anissa April; Sari, Shinta Nofita (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2025)
The development of information and communication technology has significantly transformed various aspects of life, including the provision and utilization of information sources in higher education institutions. Libraries, as centers of learning resources, are required to adapt to these changes, one of which is through the provision of electronic resources (e-resources). This study aims to analyze how the utilization of e-resources services at the University of Andalas Library contributes to increasing students' reading interest. Using a quantitative descriptive method, the research involved a sample of 100 respondents from various faculties. The results show that e-resources such as e-journals and e-books are the most frequently accessed types of digital collections by students. There is a significant positive correlation (r = 0.631, p = 0.000) between the frequency of e-resources usage and students' reading interest. However, challenges such as limited digital literacy and lack of training still hinder optimal usage. The findings highlight the strategic role of university libraries in promoting academic literacy by enhancing access, conducting information literacy training, and adopting user-centered service strategies.